Polarisation of atmospheric bremsstrahlung - Rausaria R.R.; Singh R.N. (My University, 2025)
THE terrestrial atmosphere is bombarded continuously by energetic charged particles of extraterrestrial origin. When a charged particle penetrates deep into the atmosphere, either its direction changes or its speed varies with respect to the local phase velocity of electromagnetic waves. These changes, caused by the dense atmosphere at altitudes of about 90-100 km, generate bremsstrahlung X rays. The flux of atmospheric bremsstrahlung X rays has been measured using balloons1-3, rockets and satellites4,5. Measurement of the atmospheric X-ray flux has become routine in the study of electron flux precipitation into the lower ionosphere6,7. The degree of polarisation of emitted radiation changes rather drastically with the changing energy of precipitating electrons and with the height of precipitation. But no effort has yet been made to measure the polarisation of atmospheric bremsstrahlung. We here show the potential importance of bremsstrahlung X-ray polarisation and its probable role in atmospheric diagnostics. © 1975 Nature Publishing Group.